Percutaneous Cholecystostomy in High-Risk Elderly Patients With Acute Cholecystitis: A Lifesaving Option. (March 2013) - Kapan, Murat; Onder, Akin; Tekbas, Guven; Gul, Mesut; Aliosmanoglu, Ibrahim; Arikanoglu, Zulfu; Aldemir, Mustafa
Purpose: To analyze the results of percutaneous cholecystostomy in in high-risk elderly patients with acute cholecystitis. Materials and Methods: Between June 2010 and May 2011, 11 patients aged over 60 who had at least 1 systemic disease and underwent percutaneous cholecystostomy were reviewed retrospectively. Results: The procedure was technically successful in 10 (90.9%) patients. Clinical improvement was achieved in 81.8% of patients within 72 hours. Two patients received emergency surgery while elective cholecystostomy was performed in 5 patients. Percutaneous cholecystostomy was performed singly in 4 (36.4%) patients. Early complication rate was 18.2%. Two (18.2%) patients died. Conclusion: Percutaneous cholecystostomy can be performed with low mortality and morbidity. Cholecystectomy should be performed in all patients with suitable general conditions due to the high recurrence rates of percutaneous cholecystostomy.